Large sharing networks and unusual injection practices explain the rapid rise in HIV among IDUs in Sargodha, Pakistan - Qureshi Salman U; Awan Ahmad B; Khan Adnan A; Razaque Ali; Zafar Syed T (BMC, 2009)
Abstract Background Of the nearly 100,000 street-based IDUs in Pakistan, 20% have HIV. We investigated the recent rise in HIV prevalence from 12 to 52% among IDUs in Sargodha despite > 70% coverage with syringe exchanges. Methods We interviewed approximately 150 IDUs and 30 outreach workers in focus group discussions. Results We found six rural and 28 urban injecting locations. Urban locations have about 20-30 people at any time and about 100 daily; rural locations have twice as many (national average: 4-15). About half of the IDUs started injecting within the past 2 years and are not proficient at injecting themselves. They use street injectors, who have 15-16 clients daily. Heroin is almost exclusively the drug used. Most inject 5-7 times daily. Nearly all injectors claim to use fresh syringes. However, they load, inject and share using a locally developed method called scale. Most Pakistani IDUs prefer to double pump drug the syringe, which allows mixing of blood with drug in the syringe. The injector injects 3 ml and keeps 2 ml (the scale) as injection fee. The injector usually pools all the leftover scale (now with some blood mixed with drug) either for his own use or to sell it. Most IDUs backload the scale they buy into their own fresh syringes. Discussion Use of an unprecedented method of injecting drugs that largely bypasses fresh syringes, larger size of sharing networks, higher injection frequency and near universal use of street injectors likely explain for the rapid rise in HIV prevalence among IDUs in Sargodha despite high level provision of fresh syringes. This had been missed by us and the national surveillance, which is quantitative. We have addressed this by hiring injectors as peer outreach workers and increasing syringe supply. Our findings highlight both the importance of qualitative research and operations research to enrich the quality of HIV prevention programs.